История философии права и история правовой мысли: вопросы соотношения - Дамирли, М.А. (Інститут держави і права ім. В.М. Корецького НАН України, 2005)
В статье анализируются проблемы соотношения истории философии права и истории правовой мысли, выделяются их общие и специфические черты. Одно из центральных мест при разграничении
этих дисциплин отведено проблеме понимания. Автор приходит к выводу, что содержание категории «смысл» имеет философско-исторический и конкретно-исторический пласты. The author analyses problems of the correlation between the history of philosophy of law and the history
of legal thought, emphasizing their general and specific features. One of the central aspects regarding the
delimitation of those disciplines is attributed to the comprehension problem. The author concludes that the
content of the category “sense” has both philosophical-historical and concretely-historical layers.